HOMA-IR value in predicting retinal microvascular dysfunction - Prayitnaningsih, Seskoati; Yuniasih, Kristina; Kautsarani, Intan; Hamid, Aulia A.; Iskandar, Agustin (Narra J, 2024)
Obesity and retinal microvasculature dysfunction are linked and impact visual acuity. The aim of this study was to determine the relationship between the HOMA-IR score and the presence of vascular dysfunction (perfusion index and flux index) of the optic nerve head (ONH) of the retina in obese patients and to determine its diagnostic performance to predict vascular dysfunction. A case-control study was conducted in 2022 involving individuals from obese and non-obese groups. Insulin resistance was measured using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) score using the levels of insulin and fasting glucose. Optical coherence tomography angiography (OCT-A) was performed to evaluate the flux index and capillary perfusion of ONH. The correlation between HOMA-IR, flux index, and capillary perfusion was assessed using Pearson’s correlation, and the diagnostic performance of HOMA-IR, including sensitivity, specificity, and the area under the curve (AUC), was measured. Logistic regression was used to identify the association between the HOMA-IR cutoff score with the presence of retinal microvascular dysfunction. A total of 80 individuals were included from each obese and non-obese group. The HOMA-IR score showed significant negative correlations with the perfusion of the superior (p<0.001), inferior (p<0.001), and outer (p=0.008) regions of the retinal of ONH. For the flux index, the HOMA-IR score had significant negative correlations with the superior (p=0.001), inferior (p<0.001), nasal (p=0.003), and outer (p=0.035) regions of ONH of the retina. The receiver operating characteristic (ROC) curve analysis for the HOMA-IR score at a cutoff value of 5.51 demonstrated an area under the curve (AUC) of 0.819, with a 95% confidence interval (CI) ranging from 0.727 to 0.912, suggesting its effectiveness in detecting vascular dysfunction. Multivariate logistic regression revealed a significant association between the HOMA-IR cutoff score of 5.51 with capillary perfusion of the superior (p=0.005) and nasal region (p=0.043), as well as the flux index of the inferior (p=0.013) and outer (p=0.022) regions of the ONH. These findings suggest that HOMA-IR is a promising biomarker for predicting retinal microvascular dysfunction in obese patients.